Forgetting, Memory, and Narrative in Joseph Conrad's Almayer's Folly. Issue 3 (1st October 2020) - Yao, Xiaoling
Abstract: As Joseph Conrad's first novel, Almayer's Folly remains underdiscussed, given how this very first novel, as Ian Watt sees it, illuminates "many of the technical problems which characterized Conrad's whole development as a novelist, including the dominant role of memory" ("Almayer's Folly" 177). At the center of Watt's observation is the place of memory — the way Conrad utilizes narrative techniques to represent it and the problems these very techniques create in communicating retrospective information to readers. Any discussion of memory is inseparable from its supposed opposite, forgetting. This paper furthers the line of inquiry shaped by Watt to explore the act of forgetting (and remembering) in great detail, as well as its intricate interplay with narrative strategies in Almayer's Folly . I argue that Almayer's hyperbolic process of forgetting through trace effacement ironically presents itself as an act that not only betrays the protagonist's intention to forget unpleasurable experiences, but also as one that proclaims its own limits. As a writer, Conrad demonstrates the complexity of forgetting through changes in style and narrative strategies. The intricate interaction between experience and expression renders Conrad's first literary attempt a work of art that is more sophisticated and ironic than many scholars contend it to be.